Caracterização microestrutural do eixo de um alargador de furo de poço de petróleo - Gomes, Ana Paula da Costa (Universidade Federal Rural do Semi-Árido, 2017)
Petroleum is one of the most widely used energy sources in the world. Three steps are required to obtain oil, prospecting, drilling and extraction. In drilling on land, probes and specific machinery are used. To drill drills and reamers are used. The reamers are formed by Reamer Pin, Cross Pin, Drive-Fit Body Bearing Blocks and Cutters. The main objective of this work was the microstructural characterization of the Reamer Pin of an oil well reamer.Reamer Pin was supplied by Schlumberger Serviços de Petróleo Ltda. During the work three samples of the shaft were extracted. The first sample was analyzed as received by the company, the second was tempered and cooled in oil and the last one was tempered and cooled in water. These samples were submitted to chemical composition analysis, X - ray diffractometry (XRD), optical microscopy and, finally, hardness and microhardness tests were performed. The results led to the conclusion that Reamer Pin is SAE 4140 steel.
Monografia
Keywords: Alargadores; Eixo; Caracterização microestrutural; Poço de petróleo; Aço SAE 4140; Reamers; Reamer Pin; Microstructural characterization; Oil well; SAE 4140 steel; ENGENHARIAS::ENGENHARIA MECANICA